TINJAUAN YURIDIS MONEY POLITIK DALAM PENYELANGGARA PEMILIHAN KEPALA DAERAH KABUPATEN BUTON TAHUN 2024 : STUDI UNDANG-UNDANG NOMOR 10 TAHUN 2016 - Faharudin Faharudin; Fauzan Muhamad (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2026)
The Regional Head Election (Pilkada) is an essential part of Indonesia's democratic system. However, in practice, money politics remains prevalent and undermines the principles of fair and honest elections. This research aims to examine the practice of money politics in the 2024 Regional Head Election in Buton Regency from a legal perspective, based on Law Number 10 of 2016 concerning the Election of Governors, Regents, and Mayors. The research employs a normative juridical method using statutory and limited field study approaches. The findings indicate that money politics still occurs widely, in forms such as giving money or goods to voters, either directly or indirectly. Although Law Number 10 of 2016 explicitly prohibits money politics and stipulates sanctions, its implementation remains ineffective due to weak supervision, poor law enforcement, and the low legal awareness of the public. Strengthening law enforcement, providing political education to the public, and enhancing participatory oversight are necessary efforts to ensure that regional elections are conducted in a clean, honest, and integrity-based manner.